Money versus debt financed regime: Evidence from an estimated DSGE model - Chiara Punzo; Giulia Rivolta (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2022)
We estimate a money-financing versus debt-financing medium-scale dynamic stochastic general equilibrium for the US with Borrower-Saver framework. Our results suggest that the share of net borrowers in a MF regime (17%) is lower than the one in a DF regime (19%). The MF regime enhances the positive effects of fiscal and risk premium shocks with respect to the DF regime. After an inflationary shock the MF regime leads to a mild recession while the DF regime leads to a temporary expansion followed by a sharp recession. The fiscal shock mainly explains the variance in output and borrower's consumption in a MF regime. The variance of the saver's consumption remains mainly linked to the risk premium shock in both regimes. In a DF regime, the wage mark-up shock plays the major role.
Keywords: E32; E42; E52; 330; Borrowers-Savers; Bayesian Estimation; Monetary Policy